The Effect of Structural Skeleton on the Internal Architecture Space (International Journal of Scientific Research and Management (IJSRM), 2019)
The study investigates the architectural space and its definition and the stages of development of the architectural space according to the previous civilizations up to our current era and then defining the internal space and its determinants. A historical study of the space and its value as well as the elements of the internal architecture all, were discussed in this study. The construction, the constructional structure its characteristics were defined and the constituents of the building as well. In addition, identifying the types of buildings in terms of from their functional and constructional aspects, and then identifying the constructional materials used in the constructional skeleton and their impact on the constructional skeleton in the design from several aspects until reaching the internal space and the factors affecting it. The research problem and the research objectives were defined, which is coming to design solutions and interrelated constructions as well as designing the buildings in a manner that respects the environment, taking into consideration the financial cost of the building, while minimizing the effects of construction, all of which on the internal space. The most important findings of the study are that the elements of the interior space are all interconnected and cannot be separated from each other; this is in order to reach the appropriate visual formation of the space. The elements of the internal space of the building should be evaluated by specialists in this field, is a first step before studying the selection of the most appropriate constructional skeletons of the building, before preparing the new engineering drawings, and choosing the most proper ways to protect the constructional elements during the processing of internal space processing to ensure that the cost will not increase.